Pengaruh Model Pembelajaran Contextual Teaching And Learning Terhadap Hasil Belajar Matematika Ditinjau Dari Berpikir Kritis - Titin Delina Harahap; Rahmad Husein; Suroyo Suroyo (Mahesa Research Center, 2021)
The aim of this study is to investigate The Effect of Contextual Teaching and Learning Model on Mathematic Achievement in terms of Critical Thinking. The type of research used a semi- experimental quantitative research method in which applying two experimental classes with the same sample characteristics. The population was all the students in Kotapinang district and the sample was 62 of the fifth grade elementary students of SDN 112224 Kotapinang. In the experiment class (CTL Model), the sample was 32 students. While in the control class (Conventional Model), the sample was 30 students. Research instrument used Achievement test of 10 questions from sturffing that conducted validity and reliability tests and questionnaire Critical Thinking of 16 statements. Based on the treatment, In the experiment class got Achievement 81,88 While in the control class got Achievement 73,11. And for the result, there was a significant effect on Mathematics Achievement. Applying CTL model in learning on the fifth grade elementary students who had high critical thinking showed that their mathematics achievement is better than that applying conventional model. So, in conclusion, applying CTL model gave better effect on mathematics achievement of the fifth elementary students in terms of critical thinking in Kotapinang district.